Case reportSolitary fibrous tumor in the oral cavity: a case report and diagnostic dilemma - Chomik, Piotr; Michcik, Adam; Michajłowski, Igor; Sobjanek, Michał; Włodarkiewicz, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
The investigators wish to discuss the diagnostic difficulties, histology and immunohistochemical profile of a solitary fibrous tumor (SFT) based on the presented case, as well as previously reported cases within the oral cavity. A young woman was referred to the Department of Maxillofacial Surgery, Medical University of Gdansk, Poland, due to a considerable palpable mass within the hard palate. Pain and discomfort caused by the tumor’s location were the main complaints. A clinical examination revealed a tumor of the right hard palate along the alveolar crest, measuring approximately 5 cm × 3 cm. Panoramic X-ray depicted a bone defect of the alveolar crest around tooth 17. Histological and immunohistochemical evaluation of the biopsy specimen and resected tumor established the diagnosis of SFT. This rare spindle cell neoplasm of mesenchymal origin is typical of serosal sites and approximately 80 cases within the head and neck region have been reported so far. The hard palate is one of the least frequent locations. Approximately 5-20% of lesions may present features of aggressiveness. The authors wish to emphasize that the diagnosis of SFT is challenging due to a relatively small number of cases reported in the literature, uncertain etiology of the tumor, as well as clinical and histological similarity to other, more frequently occurring benign neoplasms of mesenchymal origin, i.e. hemangiopericytoma, myofibroblastoma, schwannoma, neurofibroma, leiomyoma, as well as inflammatory disorders, especially nodular fasciitis. Radical excision of the tumor is mandatory for effective treatment due to the possibility of recurrence and malignant transformation after subradical resection.